An impact review of a Western Australian research translation program. - Abby Mosedale; Elizabeth Geelhoed; Yvonne Zurynski; Suzanne Robinson; Kevin Chai; Delia Hendrie (PLoS ONE, 2022)
The translation gap between knowledge production and implementation into clinical practice and policy is an ongoing challenge facing researchers, funders, clinicians and policy makers globally. Research generated close to practice and in collaboration with end users is an approach that is recognised as an effective strategy to facilitate an improvement in the relevance and use of health research as well as building research capacity amongst end users. The Research Translation Projects (RTP) program funded by the Western Australian (WA) Department of Health facilitates clinical and academic collaboration through competitive funding of short-term research projects. Its aim is to improve healthcare practice while also finding efficiencies that can be delivered to the WA health system. A mixed methods approach was adopted to evaluate the research impact of the RTP program, at completion of the two-year funding period, across a range of impact domains through the adaptation and application of the Canadian Academy of Health Sciences' (CAHS) framework for research impact. In addition, further analysis was undertaken to address specific objectives of the RTP program more closely, in particular research capacity building and collaboration and health system Inefficiencies targeted by the program. Social network analysis was applied to assess the extent and growth of collaboration across WA health organisations over time. Results indicated that the 'bottom up' approach to research translation has triggered modest, yet positive outcomes across impact domains including advancing knowledge, collaboration and capacity building as well as contributing to changes in policy and practice. Additionally, the projects identified opportunities by which inefficiencies in the health system can be addressed. Further work is required to better understand the pathways by which short-term outcomes can be translated into more long-term impacts and the mechanisms that trigger this process.